A Novel Liquid Chromatography Tandem Mass Spectrometry Technique using Multi-Period-Multi-Experiment of MRM-EPI-MRM3 with Library Matching for Simultaneous Determination of Amphetamine Type Stimulants Related Drugs in Whole Blood, Urine and Dried Blood Stain (DBS)—Application to Forensic Toxicology Cases in Malaysia - Zubaidi, Fathiah A.; Choo, Yeun Mun; Tan, Guan Huat; Hamid, Hamimah Abd; Choy, Yap Ken (Oxford University Press, 2019)
A novel mass spectrometry detection technique based on a multi-period and multi- experiment (MRM-EPI-MRM3) with library matching in a single run for fast and rapid screening and identification of amphetamine type stimulants (ATS) related drugs in whole blood, urine and dried blood stain was developed and validated. The ATS-related drugs analyzed in this study include ephedrine, pseudoephedrine, amphetamine, methamphetamine, MDMA (3,4-Methylenedioxymethamphetamine), MDA (3,4-Methylenedioxyamphetamine), MDEA (3,4-Methylenedioxy-N-ethylamphetamine) and phentermine. The relative standard deviation for inter and intraday was less than 15% while recoveries ranged from 80% to 120% for all three matrices, i.e., whole blood, urine and dried blood stain. All compounds gave library matching percentage of more than 85% based on the purity. This method was proven to be simple and robust, and provide high confident results complemented with library matching confirmation.